Exploring the relationship between school-level teacher qualifications and teachers' perceptions of school-based professional learning community practices. (February 2016) - Ho, Dora; Lee, Moosung; Teng, Yue
Abstract: This study explores the relationship between school-level teacher qualifications and school-based professional learning community (PLC) practices in Early Childhood Education in Hong Kong. A territory-wide survey examined how preschool teachers perceived shared responsibility, reflective dialogues, deprivatized practices and organizational learning. The findings suggest a significant relationship between school-level teacher qualifications and teachers' perceptions of school-based PLC practices. As the percentage of bachelor degree holders in preschools increases, teachers are more positive about PLC practices in their perceptions. This study establishes a platform for future studies focusing on structural relationships between teacher qualifications and school-based PLC practices. Highlights: The link between school-level teacher qualifications and school-based professional learning community in ECE was examined. The relationship between school-level teacher qualification and school-based PLC activities was significant. As the percentage of bachelor degree holders increased, the level of teachers' perceptions of the PLC activities increased.